Power Dynamics and Multi-Stakeholder Collaborative Governance: Unveiling Stakeholder Interests in the Citarum Harum Program - Dwi Agus Sumarno (Khazanah Sosial, 2025)
This study aims to analyze the dynamics of power and multi-stakeholder collaborative governance in the Citarum Harum Program using the Regulatory Capture approach, focusing on information asymmetry, collusion, and regulatory consequences. This study used a qualitative and case study approach. The documents analyzed were purposively selected based on temporal proximity (2019-2025), thematic relevance to regulatory capture, and source credibility. Data were analyzed using a thematic analysis approach. Triangulation was applied by comparing findings from scientific articles, government documents, NGO reports and media articles to ensure data consistency. Findings reveal that unverified industry-dominated data biases policy decisions, while collusion in project procurement limits access for small industries and local communities. Weak oversight mechanisms exacerbate regulatory transparency issues, affecting program effectiveness. Despite an increase in the Citarum River Water Quality Index from 33.43 (2018) to 50.78 (2023), pollution remains a critical challenge. As a scientific contribution, this study proposes the Citarum Sustainable Governance Model (CSGM) with six key components: (1) Digital transparency via e-Government, ensuring all procurement stages are digitally recorded and independently audited; (2) Citarum Sustainability Council Forum, fostering multi-stakeholder collaboration through periodic discussions on budget allocation, project progress, and policy evaluation; (3) Community-based audits via e-governance, where trained local communities monitor and report discrepancies through an established platform; (4) Transparent law enforcement, including an environmental court and a secure whistleblower system to report violations; (5) Incentive and education programs, providing micro-grants and continuous training to enhance environmental monitoring capacity; and (6) A reward and sanction system for regulators and contractors, where ethical performance is incentivized while collusion results in penalties. This model aims to mitigate regulatory capture, enhance transparency, and strengthen a fair and sustainable environmental governance framework.